Model Komunikasi Ritual Agama pada Pembelajaran Pendidikan Agama Islam dalam Membangun Inklusivisme Beragama - Ali Ahmad Yenuri (Institut Agama Islam Al-Hikmah Tuban, 2022)
The study of the research aims to describe and interpret the form of religious rituals carried out at Setia Budhi Gresik Elementary School, as well as ritual communication models for building religious inclusiveness. This research provides benefits including: (1) enriching theoretical studies on PAI learning communication in a school environment where students are multi-religious; and (2) clarifying the content of inclusivism in the content of PAI materials and learning. The results showed that the religious rituals expressed in PAI learning contained an inclusive message. It can function as a multicultural learning because the ritual communication is not only intended as a religious expression, but as an expression of harmony and togetherness because they can cooperate with each other in celebrating their respective religious rituals. Understanding, values, and inclusive attitudes can also be found in the learning communication. In general, PAI materials contain inclusive understanding, values, and attitudes. Even though there is an exclusivity side of a religion, such as divinity, prophethood, and religion, they are able to communicate well, so that inclusivism can still emerge